KONSUMSI BAHAN KERING DAN BAHAN ORGANIK KAMBING KACANG JANTAN YANG DIBERI NAUNGAN DAN TANPA NAUNGAN - Merianse Djita; Bambang H. Sutanto; Cardial L.O. Leo-Penu (Politeknik Pertanian Negeri Kupang, 2019)
This study used 14 Kacang male goats at same age. The animals were randomly divided into two groups, namely 1) the pen with shade and 2) and the pen without shade. The results showed that Kacang goats stayed in the pen with and without shade were not different in dry matter consumption (267.25 g/d/h and 266.84 g/d/h repectively) and organic matter consumption(178.74 g/d/h and 180.83 g/d/h repectively). In conclusion, farmed goat Kacang in the pens with and without shade have a relatively similar consumption of dry matter and organic matter. However, water consumption of the shaded goat group was much higher compared to the unshaded goat group.